2009
DOI: 10.1227/01.neu.0000345631.54446.06
|View full text |Cite
|
Sign up to set email alerts
|

Medial Forebrain Bundle Stimulation as a Pathophysiological Mechanism for Hypomania in Subthalamic Nucleus Deep Brain Stimulation for Parkinson's Disease

Abstract: We hypothesize that STN DBS-induced reversible acute hypomania might be elicited by inadvertent and unilateral coactivation of putative limbic STN tributaries to the MFB. These findings may provide insight into the neural pathways of hypomania and may facilitate future investigations of the pathophysiology of mood disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
159
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(171 citation statements)
references
References 27 publications
7
159
0
2
Order By: Relevance
“…We observed that brainstem pathways in the tegmentum of the medulla and pons sampled in this study converge into newly described caudal and rostral divisions of an MHB in the midbrain, and in turn, into the MFB on either side of the third ventricle. Recently, the MFB was visualized for the first time in the human brain with diffusion tractography (Coenen et al, 2009(Coenen et al, , 2012 and was shown to traverse the anterior limb of the internal capsule on its way to the prefrontal cortex. We confirmed the capsular trajectory of the slMFB and its prefrontal connections, but we also visualized connections with the insula and superior temporal gyrus, two forebrain targets that are known to contribute to homeostatic regulation.…”
Section: Human Central Homeostatic Network 195 Discussionmentioning
confidence: 99%
“…We observed that brainstem pathways in the tegmentum of the medulla and pons sampled in this study converge into newly described caudal and rostral divisions of an MHB in the midbrain, and in turn, into the MFB on either side of the third ventricle. Recently, the MFB was visualized for the first time in the human brain with diffusion tractography (Coenen et al, 2009(Coenen et al, , 2012 and was shown to traverse the anterior limb of the internal capsule on its way to the prefrontal cortex. We confirmed the capsular trajectory of the slMFB and its prefrontal connections, but we also visualized connections with the insula and superior temporal gyrus, two forebrain targets that are known to contribute to homeostatic regulation.…”
Section: Human Central Homeostatic Network 195 Discussionmentioning
confidence: 99%
“…Previous reports have already implicitly used this technique and may serve as further validation. 6,21,22 We estimated the spatial accuracy of registered preoperative MR imaging and pre-and postoperative CT with the creation of individual fiber tracts to be better than 1.5 mm. All herewith presented results have to be judged and discussed within this precision.…”
Section: In Vivo Validationmentioning
confidence: 99%
“…Stimulation of the inferior and medial STN corresponding to the limbic subnucleus of the STN has been proposed as a likely structure. Our own studies also suggest the medial forebrain bundle as a candidate (Coenen et al, 2009). Clinically, stimulation induced hypomania can usually be improved by either reducing the volume of tissue activated or by stimulating a more dorsal contact.…”
Section: Subthalamic Nucleus -Stnmentioning
confidence: 55%